Healthcare professionals' perceptions of psychosocial support for family members in palliative care inpatient units-A qualitative descriptive study - Anu Soikkeli‐Jalonen; Kaisa Mishina; Heli Virtanen; Andreas Charalambous; Elina Haavisto (Wiley, 2023)
Abstract Aim This study aimed to describe the psychosocial support healthcare professionals in specialist palliative inpatient units provide to family members of palliative care patients. Design A qualitative descriptive design. Method The data were collected with focus group interviews and analysed with inductive content analysis. Results Altogether, 48 healthcare professionals, including physicians, registered nurses and practical nurses, participated in the study. Information sharing was recognised as an essential element of support. Methods to improve support of family members included an opportunity to allocate recourses to the families, systematic support and strengthening healthcare professionals' competence in family care. The healthcare professionals describe their perceptions of psychosocial support for family members primarily through patient care and the patient's situation rather than family needs. Direct support for the family members is realised principally by information sharing and conversations. Healthcare professionals express their opportunities to implement support focusing on family members' needs restricted by reason of organisational resources. The information can be used when developing and improving family care in palliative care context to recognise the most relevant needs from healthcare professionals' perspective and also when implementing healthcare professionals' education and training.